Country of origin labeling and structural change in U.S. imports of Canadian cattle and beef - Twine, Edgar E.; Rude, J.; Unterschultz, J. (Wiley, 2016)
Mandatory country of origin labeling (COOL) has become a thorny issue in U.S.–Canada bilateral trade relations. We undertake an ex post investigation of the impact of the law on U.S. imports of Canadian beef, feeder, and fed cattle. Using a partial equilibrium framework, we derive U.S. import demand equations for Canadian cattle and beef, and employ the Bai and Perron (1998, 2003) procedure for detecting multiple structural breaks with break points being endogenously determined. We find evidence that COOL may have caused significant structural change in U.S. imports of Canadian feeder and fed cattle.